Contemporary Tort Theory and Tort Law's Evolution. Issue 2 (August 2019) - Murphy, John
Abstract: Although grand, explanatory theories of tort law come apart from one another in many ways, they also have a fair amount in common. One core claim found in the work of various Kantian theorists, as well as a number of leading rights theorists, is that tort law develops, incrementally, in such a way as to achieve ever greater coherence (where such coherence is measured according to key tenets of the particular theories). This article takes issue with that claim. It shows, by reference to a host of legal landmarks, that tort law neither does, nor must, develop in this way. A great many important innovations in tort cannot be reconciled with central aspects of the theories in view, but they are easily explained by reference to major changes in material conditions of life, shifts in the ideological Zeitgeist, judicial partiality and juristic influence. As long as such factors are free to exert their influence – and there is nothing to suggest that they are not so free – it is implausible to suggest that tort law will inexorably move towards a state of ever greater coherence.